E-Governance in Community Colleges: Examining Knowledge and Effectiveness - Mainali, Hari Lal; Mainali, Basu Dev (Chaturbhujeshwar Academic Journal, 2025)
This study aims to examine students’ knowledge and perceptions of e-governance in community colleges, emphasizing its role in enhancing transparency, accountability, and administrative efficiency. Depending upon the Technology Acceptance Model (TAM) and Digital Divide Theory (DDT), the research employs a quantitative, realism based ex-post facto research. Data were generated from 136 students through simple random sampling using structured questionnaires after informed consent. Statistical analyses, including chi-square and independent samples t-tests, reveal that students possess moderate knowledge of e-governance, demonstrating greater familiarity with technological aspects than governance strategies. The findings suggest that while community colleges are advancing toward digital transformation, progress remains hindered by infrastructural and educational gaps. The study recommends integrating governance topics into curricula, implementing digital literacy programs, and enhancing ICT infrastructure to ensure sustainable e-governance adoption.